Hope during the COVID-19 outbreak: coping with the psychological impact of quarantine. Issue 3 (2nd October 2021) - Laslo-Roth, Roni; George-Levi, Sivan; Margalit, Malka
ABSTRACT: The COVID-19 outbreak and the worldwide lockdown policy have an impact on citizens in different countries. Social isolation has been difficult for many people, and especially to those experiencing quarantine. To identify protective factors from negative outcomes of the quarantine, this study examined the mediation of internet-focused coping, hope and loneliness, in the relationship between staying in quarantine and experiencing psychological distress. A total of 275 participants were divided into two subgroups – those who were in quarantine and those who were not – and all completed the following questionnaires: internet-focused coping, loneliness, hope, and brief symptom inventory scales. Results revealed that individuals who were in quarantine reported higher levels of distress than did the comparison group. The mediation model demonstrated that being in quarantine was related to higher levels of internet-focused coping, and higher levels of psychological distress. The mediation of hope predicted decreased distress, whereas loneliness predicted increased distress. The results have important practical implications for people who have experienced staying in quarantine. Identifying their psychological resources may help to reduce their vulnerability to distress. Focused interventions with hope orientation may start positive activation of personal strengths that is crucial for growth and adjustment.